2022
DOI: 10.1007/s40121-022-00645-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-World, Multicenter Case Series of Patients Treated with Oral Omadacycline for Resistant Gram-Negative Pathogens

Abstract: Introduction: Antibiotic-resistant Gram-negative bacteria have been associated with substantial morbidity and mortality and have limited treatment options available. Omadacycline (OMC) is an aminomethylcycline antibiotic that has been shown to exhibit broad in vitro activity against antibiotic-resistant Gram-negative bacteria. Given the lack of realworld data, the primary objective of our report was to describe early experience with OMC for the treatment of resistant Gram-negative infections. Methods: This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As such, eravacycline (and tigecycline) are generally avoided for bloodstream infections [ 7 ]. Omadacycline shows in vitro activity against A. baumanni , but its activity is reduced against drug-resistant strains and clinical data are limited to case series [ 61 , 62 ]. While omadacycline has some favorable characteristics (oral formulation and well-tolerated), its poorer in vitro activity compared with eravacycline against drug-resistant strains and limited clinical data are why it is not recommended for treatment of CRAB infections [ 7 ].…”
Section: Results For Sulbactam–durlobactam Compared With Other Antibi...mentioning
confidence: 99%
“…As such, eravacycline (and tigecycline) are generally avoided for bloodstream infections [ 7 ]. Omadacycline shows in vitro activity against A. baumanni , but its activity is reduced against drug-resistant strains and clinical data are limited to case series [ 61 , 62 ]. While omadacycline has some favorable characteristics (oral formulation and well-tolerated), its poorer in vitro activity compared with eravacycline against drug-resistant strains and limited clinical data are why it is not recommended for treatment of CRAB infections [ 7 ].…”
Section: Results For Sulbactam–durlobactam Compared With Other Antibi...mentioning
confidence: 99%
“…In recent years, multidrug-resistant (MDR)/extensively drug-resistant (XDR) bacteria have also been isolated from cSSTIs (such as MDR/XDR Enterobacteriaceae ) [ 35 ]. A multicenter, observational study involving nine patients has found that oral OMC (450 mg loading dose plus 300 mg maintenance dose) is effective against MDR E. coli and K. pneumoniae -induced bone/joint or intra-abdominal infection [ 37 ]. Since LZD is not active against Gram-negative pathogens [ 38 , 39 ], patients with sole Gram-negative pathogenic bacterial infections were excluded from RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Of great interest is its oral administration. A multicentre study reported nine cases treated with oral OMA, mainly osteoarticular or intra-abdominal infections caused by MDR or XDR AB CRAB, with promising results [141 ▪ ].…”
Section: What Is the Role Of Old And New Tetracyclines?mentioning
confidence: 99%